PENGARUH ATRAKSI WISATA, FASILITAS DAN KUALITAS PELAYANAN TERHADAP KEPUASAN PENGUNJUNG DI TAMAN MARGASATWA RAGUNAN JAKARTA - Stevianus Stevianus (Jurnal Ilmiah Ekonomi Bisnis, 2015)
This research is motivated by the growth rate of the high tourist in Jakarta that is not matched by an increase in the number of tourists are balanced. The problem in this research is "whether there is the influence of the tourist attractions, facilities and quality of service to customer satisfaction in the Garden Ragunan Jakarta.Yang specifically focused on three variables: the tourist attractions, facilities and quality of service. The purpose of this research is to study the effect of the three variables in influencing customer satisfaction in the Garden Ragunan Jakarta. After conducting a literature review and hypothesis formulation, data collected through questionnaires at 100 Park visitor Ragunan Jakartayang obtained using systematic sampling technique. Then do the analysis of data obtained by using multiple regression analysis. This analysis includes: validity and reliability, the classical assumption test, multiple regression analysis, hypothesis testing via t-test and F, and coefficient of determination (R2). F test showed that the variables that have a significant effect tourist attractions terjhadap visitor satisfaction and other variables not only a significant and positive effect on customer satisfaction. Figures adjusted R-square of 0.20 indicates that 20 percent of visitor satisfaction variables can be explained by the three independent variables in the regression equation. While the remaining 80 percent is explained by other variables outside the three variables used in this study. Keywords: visitor satisfaction, tourist attractions, facilities, quality of service